A novel framework for quantifying the clinical impact of substandard and falsified antimicrobials: Application to typhoid fever - Sean Cavany; Lawrence Adipo; Kerlijn van Assche; Celine Caillet; Christiane Dolecek; Cathrin Hauk; Jessica Mendes; Stella Nanyonga; Nicole Stoesser; Paul N. Newton; Christopher M. Parry; Ben S. Cooper (PLOS Global Public Health, 2026)
Substandard and falsified (SF) medicines are a neglected public health threat, with an estimated 7% of antimicrobials in low- and middle-income countries being SF. However, quantifying their clinical impact remains challenging. We developed a general framework for estimating population-level impacts of SF antimicrobials on patient outcomes and apply it to SF fluoroquinolones in typhoid treatment. The framework combines two data sources: published surveys of antimicrobial quality to characterize the distribution of active pharmaceutical ingredient (API) content and individual-level patient data to estimate dose-response relationships. These are synthesized to evaluate population-level impacts. We extracted data from surveys of fluoroquinolone quality and fitted generalized additive models to data from seven clinical trials to estimate the causal effect of ofloxacin dose on typhoid outcomes. Application to typhoid demonstrated that while dose had negligible overall effect within trial dose ranges, lower doses worsened outcomes for non-susceptible strains. When the minimum inhibitory concentration was 1 mg/L, ofloxacin matching observed ofloxacin quality (mean %API = 102.8%) improved fever clearance by 4.1 hours (90% CrI: 0.75–8.7) compared to 100% API. At the same minimum inhibitory concentration, ofloxacin whose %API instead matched the ciprofloxacin surveys (mean %API = 93.6%) worsened fever clearance by 11 hours (90% CrI: 1.9–25). This framework can quantify the impact of SF antimicrobials on different pathogen–antimicrobial pairs. For typhoid, it demonstrates that SF fluoroquinolones likely have a substantial impact on treatment outcomes in settings like South Asia where non-susceptible strains are prevalent. Increased vigilance around antimicrobial quality is important in such settings.